1990
DOI: 10.1002/jbmr.5650050409
|View full text |Cite
|
Sign up to set email alerts
|

Human lactation: Forearm trabecular bone loss, increased bone turnover, and renal conservation of calcium and inorganic phosphate with recovery of bone mass following weaning

Abstract: The calcium (Ca) metabolism of established human lactation was studied in 40 adult women (mean age 32.4 years) who had been breast-feeding for 6 months (Lac) and in 40 age-matched controls (Con) using fasting urine and blood biochemistry and forearm single-photon bone mineral densitometry (BMD). Serial studies were performed up to 6 months after weaning in Lac women and repeated once in Con women. During lactation the significant findings were (1) a selective reduction (7.1%, P less than 0.03) in BMD at the ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
121
0
4

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 224 publications
(134 citation statements)
references
References 39 publications
9
121
0
4
Order By: Relevance
“…Longitudinal studies in both BF and NBF women have demonstrated elevations in markers of both bone formation and resorption in the first weeks postpartum compared with measurements made in the same individual before pregnancy (39,67,104,109) , in late pregnancy (112) , 1 year after delivery (113) , postweaning (71,87) or 1 year after resumption of menses (114) . In cross-sectional studies higher concentrations of bone turnover markers than in NPNL women have been reported during the first weeks postpartum (93,104,115,116) . The patterns of change in the various bone turnover markers postpartum are influenced by lactation; at the same time points BF women have higher concentrations of all markers than NBF mothers (72,91,95,116,117) .…”
Section: Maternal Bone Mineral Mobilisation: Bone Turnover Studiesmentioning
confidence: 95%
See 4 more Smart Citations
“…Longitudinal studies in both BF and NBF women have demonstrated elevations in markers of both bone formation and resorption in the first weeks postpartum compared with measurements made in the same individual before pregnancy (39,67,104,109) , in late pregnancy (112) , 1 year after delivery (113) , postweaning (71,87) or 1 year after resumption of menses (114) . In cross-sectional studies higher concentrations of bone turnover markers than in NPNL women have been reported during the first weeks postpartum (93,104,115,116) . The patterns of change in the various bone turnover markers postpartum are influenced by lactation; at the same time points BF women have higher concentrations of all markers than NBF mothers (72,91,95,116,117) .…”
Section: Maternal Bone Mineral Mobilisation: Bone Turnover Studiesmentioning
confidence: 95%
“…However, BF mothers nursing twins have elevated plasma concentrations of both PTH and 1,25(OH) 2 D compared with those nursing single infants (193) . Elevated PTH and 1,25(OH) 2 D have been reported in BF women relative to early lactation and to NPNL women during the later stages of lactation and after breast-feeding stops (83,95,109,113,115,144,190,191) , although the pattern is not consistent. The increases in PTH and 1,25(OH) 2 D may play a role in the replenishment of bone mineral postlactation through their effects on intestinal absorption and renal retention of Ca.…”
Section: Lactation and Postpartummentioning
confidence: 96%
See 3 more Smart Citations